Effect of photoperiod, lunar cycle and some environmental factors on gestation and parturition time in purebred and crossbred goats (F1, F2 and B1 generations) - Erduran, H (Journal of the Hellenic Veterinary Medical Society, 2025)
The aim of this study was to investigate the effects of photoperiod, lunar cycle and various environmental factors on gestation period and parturition time in 624 kids born to Hair and Saanen × Hair and Alpine × Hair crossbred goats (F1, F2 and B1). The effects of maternal genotype, parity, kid genotype, sex, birth type, flock and year factors on the time of birth were found to be significant (p<0.05). The majority of births (83.5%) occurred during daylight hours. The effect of lunar cycle and light/dark nights on the time of birth showed statistically significant differences (p<0.05). During the new moon phase, only 8% of births were recorded at their lowest, while the highest number of births (19%) was recorded during the waning gibbous moon phase (p<0.05). In addition, the birth frequency for goats was higher in the light nights than in the dark nights (p<0.01). Moon phase, parent genotype, and birth type affected gestation length of goats (p<0.01). Parturition time and lunar cycle proved to be significant factors affecting the gestation period (p<0.05). A shorter gestation period was observed in goats exposed to higher levels of moonlight. The study revealed that environmental factors significantly influence gestation period and parturition time. In addition, the lunar cycle and photoperiod also have a significant effect on these parameters. The results suggest that potential environmental effects should be carefully considered in studies investigating goat reproduction.